2013
DOI: 10.1186/1471-2202-14-45
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular input patterns in the mouse olfactory bulb evoked by retronasal odor stimuli

Abstract: BackgroundOdorant stimuli can access the olfactory epithelium either orthonasally, by inhalation through the external nares, or retronasally by reverse airflow from the oral cavity. There is evidence that odors perceived through these two routes can differ in quality and intensity. We were curious whether such differences might potentially have a neural basis in the peripheral mechanisms of odor coding. To explore this possibility, we compared olfactory receptor input to glomeruli in the dorsal olfactory bulb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 83 publications
(118 reference statements)
4
34
0
Order By: Relevance
“…These two modes of olfaction are associated with two overlapping but separate neural networks ( Small et al, 2005 ). Studies further indicate that retronasal smell, at both threshold and suprathreshold odor concentrations, is less sensitive than orthonasal smell in humans ( Heilmann and Hummel, 2004 ; Hummel et al, 2006 ; Furudono et al, 2013 ). These sensitivity differences may in part be explained by difference in direction-dependent flow patterns across the olfactory epithelium ( Zhao et al, 2006 ) in interaction with flow rate and non-uniform receptor distributions ( Schoenfeld and Cleland, 2006 ), in addition to differences in higher level mechanisms as learning ( Bender et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two modes of olfaction are associated with two overlapping but separate neural networks ( Small et al, 2005 ). Studies further indicate that retronasal smell, at both threshold and suprathreshold odor concentrations, is less sensitive than orthonasal smell in humans ( Heilmann and Hummel, 2004 ; Hummel et al, 2006 ; Furudono et al, 2013 ). These sensitivity differences may in part be explained by difference in direction-dependent flow patterns across the olfactory epithelium ( Zhao et al, 2006 ) in interaction with flow rate and non-uniform receptor distributions ( Schoenfeld and Cleland, 2006 ), in addition to differences in higher level mechanisms as learning ( Bender et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, odor concentration has been shown to be directly proportional to perceived odor intensity, as well as olfactory receptor neuron population responses ( Lapid et al, 2009 ). While odor identity coding during orthonasal smell has been fairly well studied ( Stewart et al, 1979 ; Rubin and Katz, 1999 ; Meister and Bonhoeffer, 2001 ; Spors et al, 2006 ; Verhagen et al, 2007 ), and ignored odor direction, studies on the retronasal odor identity coding have only recently begun ( Scott et al, 2007 ; Gautam and Verhagen, 2012b ; Furudono et al, 2013 ). Furthermore, a systematic study of the coding of retronasal odor intensities in the olfactory bulb (OB) of any species is yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…We focused as much as possible on orthonasal perception of odors and did not account for the description of flavors. The retronasal perception of numerous odorants differs from their orthonasal perception, and some hypotheses have been proposed to explain this difference, which remains unclear …”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that smelling novel odors increased c-Fos expression in piriform cortex (Illig and Haberly, 2003) and odor-evoked responses habituate with experience (Wilson, 1998); however, odors were only presented orthonasally (detection of odors via inhalation). Retronasal olfaction is necessary for odor-taste associations and differs from orthonasal olfaction both perceptually (Heilmann and Hummel, 2004; Hummel et al, 2006) and physiologically (Furudono et al, 2013; Gautam and Verhagen, 2012b). For example, food odors given retronasally, even in the absence of liquid, are localized to the mouth (Lim and Johnson, 2012) and the controlled delivery of odors orthonasally or retronasally evoked different patterns of activity in the olfactory bulb (Gautam et al, 2014).…”
Section: Discussionmentioning
confidence: 99%